NATIONAL SECURITY OF THE REPUBLIC OF SERBIA - Gerginova, Tatjana (Horizons - International Scientific Journal, 2020)
Within the framework of this paper, the author determines the national security of the Republic of Serbia through the analysis of the Strategy of National Security of Serbia from 2009 and 2019. In the introductory part of the paper, the author defines the terms "security policy" and "strategy". Furthermore the author determines the national security policy in Serbia according to the strategy from 2009 and 2019 and provides an analysis of the according to the strategy from 2009 and 2019 and provides an analysis of the environment of the Republic of Serbia, identifies challenges, risks and dangers to security, identifies national interests, sets goals, basic principle and policy elements of national security. In preparing the content of the paper, the author will use the method for content analysis and the historical method. The content will be based on an analysis of foreign literature and the use of electronic content. The subject of research in this paper is the national security of the Republic of Serbia in modern global conditions. The purpose of this study paper is the importance of national security and global security in the scientific literature.